Pengaruh Variasi Konsentrasi Garam terhadap Kualitas Fermentasi Udang - yuktika, siti; sutiyanti, ekris; dhewi, endha sukma; martika, shinta dwi; sa'diyah, rizqa damas (Bioedukasi: Jurnal Pendidikan Biologi, 2017)
AbstractShrimp is one source of protein that people like. Shrimps have major weaknesses that are susceptible to decay due to physiological, mechanical, and microbiological influences. One effort to process and preserve the simple and easy fishery is fermentation. The salt concentration used in shrimp fermentation greatly determines the quality of the shrimp. The purpose of this study was to determine the effect of salt concentration (20%, 25% and 30%) on shrimp fermentation process for seven days. The method used in this study is experimental and the parameters used in this research are temperature, pH, total organic acid, microbiological analysis and organoleptic test (including aroma, taste and texture). The results show that shrimp fermentation with 25% concentration has the best quality compared to shrimp fermentation that use concentration 20% and 30%.Keywords: shrimp, fermentation, salt concentration.